Modified graphite material, preparation method thereof, negative electrode sheet, secondary battery and electric device

CN122957833APending Publication Date: 2026-10-23WANHUA CHEM GRP BATTERY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510505586.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0002]人造石墨是锂离子电池负极材料的一种,其具有较高的容量、良好的循环性能等特点,但是人造石墨表面存在着较多活性端面,在锂离子电池充放电过程中,电解液会在活性端面上发生分解反应以及溶剂分子的嵌入,破坏石墨结构导致其性能下降

Benefits of technology

[0033]本申请实施例中改性石墨材料的制备方法通过氧化人造石墨得到表面含氧官能团的改性人造石墨,再将改性人造石墨与含有羟基基团的氟碳树脂通过化学键键合得到包覆前驱体,实现对人造石墨的包覆。最后将包覆前驱体碳化得到包含C-F键的硬碳包覆改性石墨材料。此外,改性石墨材料的制备过程相对酸处理黑滑石制备含C-F键碳材料时用酸量大,本申请实施例中改性石墨材料的制备方法对环境友好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957833A_ABST
    Figure CN122957833A_ABST
Patent Text Reader

Abstract

Embodiments of the present application provide a modified graphite material, a preparation method thereof, a negative electrode sheet, a secondary battery and an electric device. The preparation method comprises: obtaining modified artificial graphite with surface oxygen-containing functional groups by oxidizing artificial graphite; bonding the obtained modified artificial graphite and fluorocarbon resin containing a hydroxyl group through a chemical bond, so that the fluorocarbon resin coats the artificial graphite to obtain a coating precursor; and carbonizing the coating precursor to obtain a hard carbon-coated modified graphite material containing C-F bonds. The method realizes coating of the graphite material through chemical bonding, and the obtained modified graphite material has better coating uniformity and good morphology and particle size distribution. The present application also provides a modified graphite material with more lithium ion storage active sites. Finally, the present application also provides application of the modified graphite material in a negative electrode sheet, a secondary battery and an electric device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery materials, and in particular to a modified graphite material and its preparation method, a negative electrode sheet, a secondary battery, and an electrical device. Background Technology

[0002] Artificial graphite is a type of negative electrode material for lithium-ion batteries, characterized by high capacity and good cycle performance. However, the surface of artificial graphite has many active end faces. During the charging and discharging process of lithium-ion batteries, the electrolyte undergoes decomposition reactions and solvent molecule intercalation at these active end faces, damaging the graphite structure and leading to a decline in performance. Coating modification of artificial graphite is a method to improve its performance, but current related technologies suffer from problems such as poor rate performance and poor coating uniformity. Summary of the Invention

[0003] This application aims to at least partially address one of the technical problems in the related art.

[0004] This application proposes a method for preparing modified graphite materials, which achieves coating of graphite materials through chemical bonding. The resulting modified graphite materials have better coating uniformity and good morphology and particle size distribution. In addition, the preparation process is environmentally friendly and can be prepared and promoted on a large scale.

[0005] In another aspect, this application proposes a modified graphite material that can be prepared on a large scale using the preparation method provided in this application. The modified graphite material is a hard carbon-coated modified graphite material containing CF bonds, which has more lithium-ion storage active sites.

[0006] This application also proposes a negative electrode sheet, which uses the modified graphite material provided in this application as the negative electrode material to obtain a negative electrode sheet with higher specific capacity and conductivity.

[0007] This application also proposes a secondary battery in which the modified graphite material provided in this application is used as the negative electrode material to obtain a negative electrode sheet. The application of this negative electrode sheet in the secondary battery greatly improves the rate performance.

[0008] The last aspect of this application proposes an electrical device that uses the modified graphite material provided in this application as a negative electrode material to obtain a negative electrode sheet, which is then applied to a secondary battery, and the resulting secondary battery is assembled and applied to the electrical device to improve the performance of the electrical device.

[0009] According to an embodiment of the first aspect of this application, a method for preparing a modified graphite material is provided, comprising the following steps:

[0010] Step 1: Oxidize artificial graphite to obtain modified artificial graphite with oxygen-containing functional groups on the surface;

[0011] Step 2: The modified artificial graphite obtained in Step 1 is chemically bonded to a fluorocarbon resin containing hydroxyl groups, so that the fluorocarbon resin coats the artificial graphite to obtain a coated precursor.

[0012] Step 3: Carbonize the coating precursor obtained in Step 2 to obtain a hard carbon-coated modified graphite material containing CF bonds.

[0013] In some embodiments, the artificial graphite Dv50 in step one has a diameter of 8-15 μm and a specific surface area of ​​1.3-1.4 m². 2 / g, tap density is 1.1-1.2g / cm³ 3 The degree of graphitization is 92-94%;

[0014] And / or, the artificial graphite is oxidized using an oxidizing agent; the oxidizing agent includes at least one of concentrated sulfuric acid, hydrogen peroxide, potassium permanganate solution, or concentrated nitric acid;

[0015] And / or, a first catalyst is added during the oxidation of the artificial graphite; the first catalyst comprises at least one of formic acid, glacial acetic acid, or propionic acid;

[0016] And / or, the mass ratio of the artificial graphite, the oxidant and the first catalyst is 1:(3-8):(0.5-1);

[0017] And / or, the temperature of the artificial graphite oxidation reaction is 40-70℃ and the time is 6-10h; after filtering, washing and drying the reaction residue, the modified artificial graphite is obtained.

[0018] In some embodiments, the fluorocarbon resin in step two has a carbon residue rate of 40-50% and a fluorine content of 15-25%, and based on the fluorocarbon resin, the content of hydroxyl groups in the fluorocarbon resin is 5-10 wt%.

[0019] And / or, the fluorocarbon resin has a weight-average molecular weight of 15,000-30,000 g / mol and a molecular weight distribution coefficient of less than 2.0.

[0020] In some embodiments, the fluorocarbon resin is prepared by dissolving a polymer composition comprising a variety of polymeric monomers and an initiator in a reaction solvent and reacting at 50-75°C for 5-12 hours.

[0021] The polymeric monomers include vinyl acetate, hydroxyethyl allyl ether, phenyl acrylate, trifluorochloroethylene, and phenethyl cinnamate, dioctyl phthalate, or diallyl phthalate; wherein, based on the polymeric composition, the hydroxyethyl allyl ether has a mass percentage of 10-15%; the trifluorochloroethylene has a mass percentage of 20-30%; and the total mass percentage of the remaining polymeric monomers is 60-70%.

[0022] And / or, based on the polymer composition, the initiator is a thermally decomposable initiator with a mass percentage of 1-5%;

[0023] And / or, the reaction solvent is a benzene-based solvent, and its mass is 1.5-2 times that of the polymer composition.

[0024] In some embodiments, in step two, under a protective atmosphere, the fluorocarbon resin and the modified artificial graphite in a mass ratio of (30-40):(200-300) are dissolved in a solvent and reacted at 80-120°C for 5-10 hours under the action of a second catalyst, and the coated precursor is obtained by vacuum distillation.

[0025] And / or, the second catalyst is dibutyltin dilaurate, di(dodecylthio)dioctyltin, or stannous isooctanoate;

[0026] And / or, the mass ratio of the second catalyst to the modified artificial graphite is (0.5-1):(200-300);

[0027] And / or, the solvent is an organic solvent; the mass ratio of the solvent to the fluorocarbon resin is (150-250):(30-40);

[0028] And / or, the organic solvent is selected from naphtha, toluene or xylene.

[0029] In some embodiments, the coating precursor described in step three is carbonized under a protective atmosphere;

[0030] And / or, the heating rate during the carbonization process of the coated precursor is 2-5℃ / min, the carbonization temperature is 700-1100℃, and the holding time is 2-5h.

[0031] In some embodiments, the coating precursor is carbonized by segmented heating, and the carbonization process includes a first carbonization process and a second carbonization process; the carbonization temperature in the first carbonization process is 500-700℃ and the holding time is 20-20min; the carbonization temperature in the second carbonization process is 700-1000℃ and the holding time is 30min-5h.

[0032] In some embodiments, the carbonization process of the coated precursor further includes a third carbonization process; wherein the carbonization temperature is 800-1100℃ and the holding time is 2-5h.

[0033] The method for preparing modified graphite materials in this application involves oxidizing artificial graphite to obtain modified artificial graphite with oxygen-containing functional groups on its surface. Then, the modified artificial graphite is chemically bonded to a fluorocarbon resin containing hydroxyl groups to obtain a coating precursor, thus coating the artificial graphite. Finally, the coating precursor is carbonized to obtain a hard carbon-coated modified graphite material containing CF bonds. Furthermore, the preparation process of the modified graphite material uses a larger amount of acid compared to the acid treatment of black talc to prepare CF-bonded carbon materials, making the method in this application environmentally friendly.

[0034] According to embodiments of the second aspect of this application, modified graphite materials obtained by the preparation method described in any of the above embodiments are proposed.

[0035] In some embodiments, the modified graphite material has a core-shell structure; its coating density is >70%, its Dv50 is 10-13 μm, and its specific surface area is 1.4-1.6 m². 2 / g, tap density is 1.2-1.3g / cm³ 3 .

[0036] The modified graphite material of this application can be rapidly prepared using the preparation method provided in this application. The CF bonds in the fluorocarbon resin give the modified graphite material more lithium-ion storage active sites. Furthermore, the carbonization process of the coating precursor may increase the internal defects of the modified graphite material, leading to an increase in active sites and more lithium storage sites. This increases the conductivity of the modified graphite material and significantly improves its rate performance. Therefore, the modified graphite material provided in this application is a hard carbon-coated modified graphite material containing CF bonds, possessing more lithium-ion storage active sites.

[0037] According to an embodiment of the third aspect of this application, a negative electrode sheet is provided, the negative electrode sheet comprising a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer comprising the modified graphite material described in any of the above embodiments.

[0038] The modified graphite material prepared in the above embodiments has more lithium-ion storage active sites and can be used in negative electrode sheets, which have higher specific capacity and conductivity.

[0039] According to an embodiment of the fourth aspect of this application, a secondary battery is provided, which includes the negative electrode sheet described in any of the above embodiments.

[0040] The modified graphite materials prepared in the above embodiments have higher specific capacity and conductivity, making the negative electrode sheets applicable to secondary batteries and improving their cycle performance and rate performance. Specifically, the coin cell secondary battery exhibits an initial reversible capacity of no less than 340 mAh / g at 0.1C, an initial coulombic efficiency of ≥92%, and a capacity retention of no less than 95% after 50 cycles at 3C.

[0041] An electrical device comprising the secondary battery described in any of the above embodiments is provided according to an embodiment of the fifth aspect of this application.

[0042] The modified graphite material prepared in the above embodiments has a negative electrode sheet with higher specific capacity and conductivity, which can be used in secondary batteries, and the resulting secondary batteries can be assembled and applied to electrical devices to improve the performance of the electrical devices.

[0043] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0044] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings, wherein:

[0045] Figure 1 This is a flowchart of a method for preparing a modified graphite material according to an embodiment of this application;

[0046] Figure 2 This is a TEM image of a hard carbon-coated modified graphite material according to an embodiment of this application. Detailed Implementation

[0047] Embodiments of this application are described in detail below. Examples of these embodiments are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application. Rather, this application includes all variations, modifications, and equivalents falling within the spirit and scope of the appended claims.

[0048] This application is made based on the following defects in related technologies: the surface of artificial graphite has many active end faces. During the charging and discharging process of lithium-ion batteries, the electrolyte will undergo decomposition reaction and solvent molecule embedding on the active end faces, which will damage the graphite structure and lead to its performance degradation.

[0049] Currently, coating modification of artificial graphite is a method to improve its performance. One related technology proposes a graphite-hard carbon coated material and its preparation method. This carbon-coated artificial graphite is made by mixing graphite and oligophenolic resin, followed by curing and pyrolysis to achieve in-situ hard carbon coating on the graphite surface, thus improving the graphite's cycling performance. However, due to the low coking value of oligophenolic resin, it easily generates large amounts of toxic and harmful gases such as CH4, H2, CO, and CO2 during production and processing, significantly impacting the environment. Furthermore, the coating uniformity cannot be guaranteed during the coating process, resulting in no significant improvement in rate performance.

[0050] In addition, related technologies also use black talc mineral as raw material and employ acid treatment to remove talc from the black talc, preparing a novel and excellent lithium-ion battery anode carbon material. This electrode material exhibits a higher specific capacity than graphite under low-rate charge-discharge conditions, but its rate performance is poor. This is because the electrochemical active sites are provided by a large number of fluorinated functional groups on the surface, thereby increasing the specific capacity of the material. However, excessive functional groups reduce the conductivity of the material, resulting in poor cycle performance and rate performance. Furthermore, although this method removes the fluorinated functional groups on the sample surface after annealing at 800℃, improving conductivity and thus improving cycle performance and rate performance, outperforming currently commercially available graphite anode materials, this method requires a large amount of acid when preparing CF-bonded carbon materials by acid treatment of black talc, which is environmentally unfriendly and difficult to industrialize. Therefore, current related technologies for coating and modifying artificial graphite suffer from problems such as poor rate performance, poor coating uniformity, and difficulty in industrialization.

[0051] Based on this, the technical solution of this application provides a modified graphite material, its preparation method, a secondary battery, and an electrical device. Regarding the preparation method of the modified graphite material, chemical bonding is used to coat the graphite material, resulting in a modified graphite material with better coating uniformity and good morphology and particle size distribution. The modified graphite material is a hard carbon-coated modified graphite material containing CF bonds, possessing more lithium-ion storage active sites. For the application of lithium manganese iron phosphate material, the modified graphite material, with its more lithium-ion storage active sites, is used as a negative electrode material to obtain a negative electrode sheet, which is then applied to secondary batteries and electrical devices.

[0052] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0054] According to an embodiment of the first aspect of this application, a method for preparing a modified graphite material is proposed, such as... Figure 1 As shown, it includes the following steps:

[0055] Step 1: Oxidize artificial graphite to obtain modified artificial graphite with oxygen-containing functional groups on the surface;

[0056] Step 2: The modified artificial graphite obtained in Step 1 is chemically bonded to a fluorocarbon resin containing hydroxyl groups, so that the fluorocarbon resin coats the artificial graphite to obtain a coated precursor.

[0057] Step 3: Carbonize the coating precursor obtained in Step 2 to obtain hard carbon-coated modified graphite material containing CF bonds.

[0058] In step one, the artificial graphite has a Dv50 of 8-15 μm and a specific surface area of ​​1.3-1.4 m². 2 / g, tap density is 1.1-1.2g / cm³ 3The degree of graphitization is 92-94%. Modified artificial graphite is obtained by oxidizing the surface of artificial graphite to generate oxygen-containing functional groups. The artificial graphite can be oxidized using an oxidizing agent, including at least one of concentrated sulfuric acid, hydrogen peroxide, potassium permanganate solution, or concentrated nitric acid.

[0059] In some embodiments, the artificial graphite is granular with a Dv50 of 8-15 μm. Examples of artificial graphite Dv50 include 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm. When the artificial graphite Dv50 is small, such as less than 8 μm, the specific surface area of ​​the artificial graphite is too large, leading to increased interfacial side reactions in the negative electrode of the resulting hard carbon-coated modified graphite material during application, which is detrimental to the cycle performance of the secondary battery. When the artificial graphite Dv50 is large, such as greater than 15 μm, the lithium-ion diffusion path in the secondary battery is too long during application of the resulting hard carbon-coated modified graphite material, which is detrimental to rate performance. Furthermore, an excessively large artificial graphite Dv50 can also lead to a decrease in the compaction density of the negative electrode, resulting in a decrease in the volumetric energy density of the secondary battery.

[0060] In some embodiments, the specific surface area of ​​the artificial graphite is 1.3-1.4 m². 2 / g. The specific surface area of ​​the example synthetic graphite is 1.3m². 2 / g, 1.4m 2 / g, etc. In some embodiments, the tap density of artificial graphite is 1.1-1.2 g / cm³. 3 The example of artificial graphite has a tap density of 1.1 m³. 2 / g, 1.2m 2 / g, etc. In some embodiments, the degree of graphitization of the artificial graphite is 92-94%. Example artificial graphite has a degree of graphitization of 92%, 93%, 94%, etc.

[0061] Artificial graphite is mixed with an oxidant and a first catalyst at a mass ratio of 1:(3-8):(0.5-1), wherein the first catalyst includes at least one of formic acid, glacial acetic acid, or propionic acid. For example, the mass ratio of artificial graphite to the oxidant and the first catalyst can be 1:(3, 4, 5, 6, 7, 8):(0.5, 6, 7, 8, 9, 1), etc. During this process, the artificial graphite, oxidant, and first catalyst are thoroughly stirred, the temperature is controlled at 40-70℃, and the reaction is carried out at atmospheric pressure for 6-10 hours. After filtration, the reaction residue, i.e., the oxidized artificial graphite filter cake, is obtained. The reaction residue is repeatedly washed with deionized water to remove residual oxidant and catalyst, and then dried in a vacuum drying oven to obtain modified artificial graphite.

[0062] In step two, the modified artificial graphite obtained in step one is reacted with fluorocarbon resin containing hydroxyl groups. The fluorocarbon resin has a char residue rate of 40-50% and a fluorine content of 15-25%. Based on the fluorocarbon resin, the hydroxyl group content of the fluorocarbon resin is 5-10 wt%. At the same time, the weight-average molecular weight of the fluorocarbon resin is 15000-30000 g / mol, and the molecular weight distribution coefficient is less than 2.0.

[0063] In some embodiments, the fluorocarbon resin is an aromatic fluorocarbon resin with a char residue of 40-50%; example fluorocarbon resins have char residues of 40%, 41%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, and 50%, etc. The char residue of the fluorocarbon resin refers to the percentage of solid carbon remaining after high-temperature pyrolysis relative to the original sample mass, reflecting its thermal stability and decomposition characteristics. In this application, thermogravimetric analysis (TGA) is used to calculate the final char residue of the fluorocarbon resin by recording the mass change curve under programmed temperature control.

[0064] In some embodiments, the fluorine content of the fluorocarbon resin is 15-25%, where the fluorine content refers to the mass percentage of all fluorine elements in the fluorocarbon resin, determined by combustion or ion chromatography. These methods are conventional detection techniques in the art and will not be elaborated further. Examples of fluorocarbon resins with fluorine contents include 15%, 16%, 17%, 18%, 19%, 20%, 20%, 21%, 23%, 24%, and 25%. When the fluorine content of the fluorocarbon resin is low, such as less than 15%, the fluorocarbon resin provides insufficient lithium-ion storage active sites; when the fluorine content is high, such as greater than 25%, it reduces the char residue of the fluorocarbon resin, thereby affecting the coating effect of the modified graphite material.

[0065] In some embodiments, fluorocarbon resin is used as a reference, wherein the hydroxyl group content of the fluorocarbon resin is 5-10 wt%; wherein the hydroxyl group content of the fluorocarbon resin is measured using near-infrared spectroscopy, and a calibration model is established based on the near-infrared spectrum of samples with known hydroxyl content for measurement. Examples of fluorocarbon resin as a reference include hydroxyl group contents of 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, etc.

[0066] In some embodiments, the molecular weight of the fluorocarbon resin is 15,000-30,000 g / mol; example fluorocarbon resins have molecular weights of 15,000 g / mol, 16,000 g / mol, 18,000 g / mol, 20,000 g / mol, 25,000 g / mol, 30,000 g / mol, etc. Furthermore, the molecular weight distribution coefficient of the fluorocarbon resin is less than 2.0, where the molecular weight distribution coefficient is a parameter describing the degree of molecular weight dispersion, defined as the weight-average molecular weight (M). w) and number-average molecular weight (M n The ratio of PDI to M w / M n This coefficient reflects the uniformity of polymer molecular chain length; the larger the value, the wider the molecular weight distribution, and vice versa.

[0067] In this application, the molecular weight and molecular weight distribution coefficient were determined using gel permeation chromatography (GPC), a technique based on the molecular sieving effect that separates polymers of different molecular weights through a column of porous gel particles. Smaller molecular weight molecules can enter the gel pores, resulting in longer elution times; larger molecular weight molecules pass through rapidly, resulting in shorter elution times. By analyzing the position and area of ​​the elution peaks, the number-average molecular weight (Mn) of the sample can be calculated. n ), weight-average molecular weight (M w ) and molecular weight distribution index (PDI = M w / M n , is a key parameter characterizing the molecular weight distribution width of a polymer. The closer its value is to 1, the more concentrated its molecular weight is, and the more stable its processing and physical and mechanical properties are.

[0068] Furthermore, the fluorocarbon resin in this application can be a self-made material. The fluorocarbon resin is prepared by dissolving a polymer composition including a variety of polymeric monomers and an initiator in a reaction solvent and reacting at 50-75°C for 5-12 hours.

[0069] The polymeric monomers include vinyl acetate, hydroxyethyl allyl ether, phenyl acrylate, trifluorochloroethylene, and phenethyl cinnamate, dioctyl phthalate, or diallyl phthalate. Based on the polymer composition, hydroxyethyl allyl ether provides hydroxyl groups during the fluorocarbon resin formation reaction, and its mass percentage is 10-15%. The mass percentage of trifluorochloroethylene is 20-30%, and the total mass percentage of the remaining polymeric monomers is 60-70%.

[0070] In this application, the polymer composition is used as the basis, and the initiator is a thermally decomposable initiator, such as azobisisobutyronitrile or azobisisoheptanenitrile, with a mass percentage of 1-5%; in this application, the reaction solvent is a benzene-based solvent, such as toluene and / or xylene, with a mass of 1.5-2 times that of the polymer composition.

[0071] In step two of this process, fluorocarbon resin and modified artificial graphite with a mass ratio of (30-40):(200-300) are dissolved in a solvent and reacted at 80-120℃ for 5-10 hours under the action of a second catalyst. The coated precursor is then obtained by vacuum distillation.

[0072] The mass ratio of fluorocarbon resin to modified artificial graphite is (3, 4): (20, 21, 23, 24, 25, 27, 28, 29, 30). When the mass ratio of fluorocarbon resin to modified artificial graphite is too small, such as less than 1:10, the coating of the resulting precursor is uneven. When the mass ratio of fluorocarbon resin to modified artificial graphite is too large, such as greater than 1:5, the resulting hard carbon-coated modified graphite material will significantly reduce the capacity and other electrochemical properties of the negative electrode sheet during application.

[0073] In this embodiment, the fluorocarbon resin and modified artificial graphite are dissolved in a solvent, wherein the solvent is an organic solvent; the organic solvent is selected from naphtha, toluene, or xylene; in some embodiments, the organic solvent is selected from xylene. The mass ratio of solvent to fluorocarbon resin is (150-250):(30-40). Example solvent to fluorocarbon resin mass ratios are (15, 17, 18, 19, 20, 21, 22, 23, 24, 25):(3, 4).

[0074] Furthermore, to further promote the chemical bonding between the fluorocarbon resin and the modified artificial graphite, a second catalyst can be added. The second catalyst is dibutyltin dilaurate, di(dodecylthio)dioctyltin, or stannous isooctanoate; and the mass ratio of the second catalyst to the modified artificial graphite is (0.5-1):(200-300). Examples of such mass ratios are (0.5, 0.7, 0.8, 0.9, 1):(200, 220, 230, 250, 260, 290, 300), etc.

[0075] For example, under a protective atmosphere, such as nitrogen, fluorocarbon resin, modified artificial graphite, and a second catalyst are added to an organic solvent and mixed thoroughly. The mixture is then heated to 80-120°C and reacted for 5-10 hours. Low-boiling-point substances are then evaporated under reduced pressure to obtain the coated precursor. The temperatures used for adding the fluorocarbon resin, modified artificial graphite, and second catalyst to the organic solvent are 80°C, 90°C, 100°C, 110°C, and 120°C.

[0076] In step three, the coating precursor obtained in step two is carbonized. The coating precursor obtained in step two is carbonized under a protective atmosphere, such as nitrogen, to obtain a hard carbon-coated modified graphite material containing CF bonds. In some embodiments, the heating rate during the carbonization process of the coating precursor is 2-5℃ / min, the carbonization temperature is 700-1100℃, and the holding time is 2-5h.

[0077] In some embodiments, the heating rate during the carbonization of the coating precursor is 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, etc. When the heating rate during the carbonization of the coating precursor is small, such as less than 2℃ / min, it will increase the energy consumption and process cost of the carbonization process. When the heating rate during the carbonization of the coating precursor is large, such as greater than 5℃ / min, the volatiles in the coating precursor will escape rapidly, which may cause internal structural defects in the coating layer of the modified graphite material. At the same time, some intermediate products will not have time to decompose and form impurities remaining in the coating layer.

[0078] In some embodiments, the carbonization temperature during the carbonization process of the coating precursor is 700℃, 800℃, 900℃, 1000℃, 1100℃, etc. When the carbonization temperature is low, such as less than 700℃, the carbonization reaction of the coating precursor is insufficient, and there are many defects in the coating layer of the modified graphite material. When the carbonization temperature is high, such as greater than 1100℃, the coating layer of the modified graphite material may shrink drastically at high temperatures, resulting in cracks.

[0079] In some embodiments, the holding time during the carbonization process of the coating precursor is 2h, 3h, 4h, 5h, etc. When the holding time for carbonization of the coating precursor is short, such as less than 2h, the carbonization reaction of the coating precursor is insufficient, resulting in an incomplete coating layer of the modified graphite material. When the holding time for carbonization of the coating precursor is long, such as greater than 5h, the coating layer of the modified graphite material may develop cracks or become too thick, which is detrimental to the rate performance and cycle performance of the secondary battery when the modified graphite material is used.

[0080] In some embodiments, the coating precursor is carbonized by staged heating, and the carbonization process includes a first carbonization process and a second carbonization process; in the first carbonization process, the carbonization temperature is 500-700℃ and the holding time is 20-20 min; in the second carbonization process, the carbonization temperature is 700-1000℃ and the holding time is 30 min-5 h. Furthermore, in some embodiments, the carbonization process of the coating precursor also includes a third carbonization process; wherein the carbonization temperature is 800-1100℃ and the holding time is 2-5 h.

[0081] In step three of this embodiment, coating layers of varying thicknesses and densities can be obtained by controlling the heating temperature and time. The CF bonds in the fluorocarbon resin give the modified graphite material more lithium-ion storage active sites, resulting in higher specific capacity at relatively low discharge / charge current densities. Furthermore, the carbonization process increases internal defects in the modified graphite material, leading to more active sites and increased lithium storage capacity. This improved conductivity significantly enhances rate performance.

[0082] Therefore, the method for preparing modified graphite materials in this application involves oxidizing artificial graphite to obtain modified artificial graphite with oxygen-containing functional groups on its surface, and then chemically bonding the modified artificial graphite with a fluorocarbon resin containing hydroxyl groups to obtain a coating precursor, thereby coating the artificial graphite. Finally, the coating precursor is carbonized to obtain a hard carbon-coated modified graphite material containing CF bonds. Compared with uncoated graphite and graphite composite materials coated with coating agents without CF bonds in related technologies, the hard carbon-coated modified graphite material containing CF bonds obtained in this application has better coating uniformity, better morphology and particle size distribution, and the coin cells prepared with it have superior cycle performance and rate performance.

[0083] Furthermore, the preparation process of modified graphite materials in related technologies requires a large amount of acid compared to the preparation of carbon materials containing CF bonds by acid treatment of black talc. The preparation method of modified graphite materials in the embodiments of this application is environmentally friendly.

[0084] According to embodiments of the second aspect of this application, a modified graphite material obtained by the preparation method in any of the above embodiments is proposed.

[0085] In some embodiments, the modified graphite material has a core-shell structure; its coating density is >70%, its Dv50 is 10-13 μm, and its specific surface area is 1.4-1.6 m². 2 / g, tap density is 1.2-1.3g / cm³ 3 .

[0086] The modified graphite material of this application can be rapidly prepared using the preparation method provided in this application. The CF bonds in the fluorocarbon resin give the modified graphite material more lithium-ion storage active sites. Furthermore, the carbonization process of the coating precursor may increase the internal defects of the modified graphite material, leading to an increase in active sites and more lithium storage sites. This increases the conductivity of the modified graphite material and significantly improves its rate performance. Therefore, the modified graphite material provided in this application is a hard carbon-coated modified graphite material containing CF bonds, possessing more lithium-ion storage active sites.

[0087] According to an embodiment of the third aspect of this application, a negative electrode sheet, a negative electrode current collector, and a negative electrode film layer disposed on at least one surface of the negative electrode current collector are provided, the negative electrode film layer comprising the modified graphite material in any of the above embodiments.

[0088] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, wherein the negative electrode film layer includes the modified graphite material in any of the above embodiments. As an example, the negative current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.

[0089] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0090] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0091] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0092] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0093] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the modified graphite material, conductive agent, binder, and any other components in any of the above embodiments, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then performing processes such as drying and cold pressing to obtain the negative electrode sheet. The modified graphite material prepared through the above embodiments has more lithium-ion storage active sites that can be used in the negative electrode sheet, which has higher specific capacity and conductivity.

[0094] According to an embodiment of the fourth aspect of this application, a secondary battery is provided, which includes the negative electrode sheet of any of the above embodiments.

[0095] The secondary battery in this embodiment includes a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. The positive electrode film layer includes the modified graphite material of the first aspect of this application. As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0096] The positive current collector may be a metal foil or a composite current collector. For example, an aluminum foil may be used as the metal foil. The composite current collector may comprise a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0097] In some embodiments, the modified graphite material layer in the positive electrode sheet of the present application does not exclude the modified graphite material provided by the present application. For example, other modified graphite materials may employ modified graphite materials well known in the art for batteries. By way of example, the modified graphite material may include at least one of the following materials: by way of example, the modified graphite material may include, but is not limited to, lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), lithium iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel type lithium manganate (LiMn2O4), spinel type lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), layered lithium manganate (LiMnO2), lithium nickelate (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium magnesate (LiMgO2), lithium calciate (LiCaO2), lithium cuprate (LiCuO2), lithium zincate (LiZnO2), lithium molybdate (LiMoO2), lithium tantalate (LiTaO2), lithium tungstate (LiWO2), lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2, 0<x<1, 0<y<1, 0<x+y<1, for example LiNi 0.8 Co 0.15 Al 0.05 O2), lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2, 0<x<1, 0<y<1, 0<x+y<1, for example LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co0.1 Mn 0.1 At least one of the following: O2, lithium-rich materials (e.g., lithium-rich nickel-cobalt-manganese oxide), manganese oxide (MnO2), vanadium oxide, sulfur oxide, silicate oxide, and their respective modified compounds. These materials may be used alone or in combination of two or more.

[0098] The modifying compounds for the aforementioned modified graphite materials can be obtained by doping, surface coating, or simultaneous doping and coating of the modified graphite materials.

[0099] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0100] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0101] In some embodiments, the positive electrode sheet can be prepared by dispersing the components used to prepare the positive electrode sheet, such as the modified graphite material, conductive agent, binder and any other components of the first aspect of this application, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0102] [Electrolytes]

[0103] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0104] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0105] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0106] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0107] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0108] The secondary battery also includes a separator. This application does not have any particular restrictions on the type of separator. Any known modified graphite material with good chemical and mechanical stability can be selected as the separator.

[0109] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0110] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0111] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0112] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0113] This application does not impose any particular restrictions on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape.

[0114] The modified graphite materials prepared in the above embodiments have higher specific capacity and conductivity, making the negative electrode sheets applicable to secondary batteries and improving their cycle performance and rate performance. Specifically, the coin cell secondary battery exhibits an initial reversible capacity of no less than 340 mAh / g at 0.1C, an initial coulombic efficiency of ≥92%, and a capacity retention of no less than 95% after 50 cycles at 3C.

[0115] An electrical device comprising the secondary battery of any of the above embodiments is provided according to an embodiment of the fifth aspect of this application.

[0116] The modified graphite material prepared in the above embodiments has a negative electrode sheet with higher specific capacity and conductivity, which can be used in secondary batteries, and the resulting secondary batteries can be assembled and applied to electrical devices to improve the performance of the electrical devices.

[0117] To facilitate a further understanding of this application, the solutions described below are further described in conjunction with embodiments. Those skilled in the art will understand that the examples described in this application are only a portion of the examples, and any other suitable specific examples are within the scope of this application.

[0118] Artificial graphite was purchased from Hunan Zhongke Xingcheng Graphite Co., Ltd. Hydrogen peroxide (30% concentration) was purchased from Beijing Innocare Technology Co., Ltd. Nitric acid (70% concentration) was purchased from Aladdin. Potassium permanganate (5% concentration) was purchased from Beijing Innocare Technology Co., Ltd. Formic acid (98% purity) was purchased from Shanghai Maclean's Biochemical Technology Co., Ltd. Glacial acetic acid (AR grade, 99.5% concentration) was purchased from Shanghai Yi'en Chemical Technology Co., Ltd. Propionic acid (≥99.5% concentration) was purchased from Shanghai Maclean's Biochemical Technology Co., Ltd. Naphtha (≥99% concentration) was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd. Toluene (analytical grade, AR) was purchased from Beijing Innocare Technology Co., Ltd. Xylene (≥99.5% concentration) was purchased from Sinopec Qingdao Refining & Chemical Co., Ltd. Dibutyltin dilaurate (95% concentration) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0119] The concentration of di(dodecylthio)dioctyltin was 98%, purchased from Shaanxi Didu New Materials Co., Ltd. The concentration of stannous isooctanoate was 95%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The purity of phenolic resin was 99%, with a carbon residue rate of 50-60%, purchased from Wuhan Jixin Yibang Biotechnology Co., Ltd. The concentration of ethanol was 95%, purchased from Jinan Mingxin Chemical Co., Ltd.

[0120] Example 1

[0121] This embodiment provides a modified graphite material, the preparation method and specific operating parameters of which are as follows: The Dv50 is 8 μm, and the specific surface area is 1.3-1.4 m². 2 / g, tap density is 1.1-1.2g / cm³ 3Artificial graphite with a graphitization degree of 92% was mixed with an oxidant and a first catalyst and stirred thoroughly. The oxidant was hydrogen peroxide, the catalyst was propionic acid, and the mass ratio of graphite, hydrogen peroxide, and catalyst was 1:4:0.7. The temperature was controlled at 70℃, and the reaction was carried out at normal pressure for 8 hours. The oxidized artificial graphite filter cake was obtained by filtration. The reaction residue was repeatedly washed with deionized water and then dried in a vacuum drying oven to obtain modified artificial graphite.

[0122] Under a nitrogen atmosphere, fluorocarbon resin with a carbon residue of 50%, a fluorine content of 15%, a hydroxyl group content of 10wt%, a weight-average molecular weight of 15000 g / mol, and a molecular weight distribution coefficient of less than 2.0, modified artificial graphite, and a second catalyst, stannous isooctanoate, were added to the organic solvent naphtha and mixed evenly. The mass ratio of fluorocarbon resin, naphtha, modified artificial graphite, and stannous isooctanoate was 1:7:10:0.033. The mixture was heated to 100℃ and reacted for 8 hours. Low-boiling-point substances were then removed by vacuum distillation to obtain the coated precursor.

[0123] The coating precursor was fed into a box furnace. Under a nitrogen atmosphere, the temperature was first increased to 500℃ at 5℃ / min and held for 30min. The second step was to increase the temperature to 700℃ at 2℃ / min and hold for 5h to obtain the modified graphite material.

[0124] Example 2

[0125] This embodiment provides a modified graphite material, the preparation method and specific operating parameters of which differ from those of Example 1 as follows: the Dv50 of the artificial graphite is 14.6 μm; the fluorine content of the fluorocarbon resin is 23.5%, the hydroxyl content is 8.5%, and the molecular weight is 21000 g / mol; the mass ratio of fluorocarbon resin to modified artificial graphite is 1:5; during the carbonization of the coating precursor, the first step is to heat to 700℃ at 5℃ / min and hold for 20 min; the second step is to heat to 800℃ at 3℃ / min and hold for 30 min; the third step is to heat to 1000℃ at 2℃ / min and hold for 2 h.

[0126] Example 3

[0127] This embodiment provides a modified graphite material, the preparation method and specific operating parameters of which differ from those of Example 1 as follows: the Dv50 of the artificial graphite is 13.7 μm; the fluorine content is 20.7%, the hydroxyl content is 6.5%, and the molecular weight is 22500 g / mol; the mass ratio of fluorocarbon resin to modified artificial graphite is 1:5; during the carbonization of the coating precursor, the first step is to heat to 600℃ at 5℃ / min and hold for 20 min; the second step is to heat to 800℃ at 3℃ / min and hold for 20 min; the third step is to heat to 900℃ at 2℃ / min and hold for 3 h.

[0128] Example 4

[0129] This embodiment provides a modified graphite material, the preparation method and specific operating parameters of which differ from those of Example 1 as follows: the Dv50 of the artificial graphite is 12.8 μm; the fluorine content is 25%, the hydroxyl content is 5%, and the molecular weight is 28090 g / mol; the mass ratio of fluorocarbon resin to modified artificial graphite is 1:8. During the carbonization of the coating precursor, the first step involves heating to 600℃ at 5℃ / min and holding for 20 min; the second step involves heating to 800℃ at 4℃ / min and holding for 30 min; and the third step involves heating to 1100℃ at 3℃ / min and holding for 2 h.

[0130] Example 5

[0131] This embodiment provides a modified graphite material, the preparation method and specific operating parameters of which differ from those of Example 1 as follows: the Dv50 of the artificial graphite is 15.0 μm; the fluorine content is 24.2%, the hydroxyl content is 7.9%, and the molecular weight is 30000 g / mol; the mass ratio of fluorocarbon resin to modified artificial graphite is 1:7. During the carbonization of the coating precursor, the first step involves heating to 600℃ at 5℃ / min and holding for 20 min; the second step involves heating to 1000℃ at 4℃ / min and holding for 30 min; and the third step involves heating to 1100℃ at 3℃ / min and holding for 2 h.

[0132] Example 6

[0133] This embodiment provides a modified graphite material, the preparation method and specific operating parameters of which differ from those of Example 1 as follows: the Dv50 of the artificial graphite is 10.5 μm; the fluorine content of the fluorocarbon resin is 20%, the hydroxyl content is 10%, and the molecular weight is 30000 g / mol; the mass ratio of fluorocarbon resin to modified artificial graphite is 1:7. During the carbonization of the coating precursor, the first step involves heating to 600℃ at 5℃ / min and holding for 20 min; the second step involves heating to 1000℃ at 3℃ / min and holding for 30 min; and the third step involves heating to 1100℃ at 2℃ / min and holding for 5 h.

[0134] Comparative Example 1

[0135] This comparative example provides an artificial graphite with the following characteristic parameters: Dv50 of 14.6 μm and specific surface area of ​​1.3-1.4 m². 2 / g, tap density is 1.1-1.2g / cm³ 3 The degree of graphitization is 92%.

[0136] Comparative Example 2

[0137] This comparative example provides a modified graphite material, the preparation method and specific operating parameters of which differ from those of Example 1 as follows: the Dv50 of the artificial graphite is 14.6 μm; using phenolic resin with a molecular weight of 21000 g / mol as a coating agent, the phenolic resin and ethanol are mixed evenly at a mass ratio of 1:5 by heating to obtain a clear solution, and then the solution is thoroughly mixed with graphite at a mass ratio of 1:10, the ethanol is removed, and the mixture is dried to obtain the coated precursor.

[0138] In the first step, the temperature is increased to 700℃ at 5℃ / min and held for 20min. In the second step, the temperature is increased to 800℃ at 3℃ / min and held for 30min. In the third step, the temperature is increased to 1000℃ at 2℃ / min and held for 2h.

[0139] Experimental Example

[0140] The modified graphite materials prepared in the above embodiments and Comparative Example 2, as well as the artificial graphite provided in Comparative Example 1, were tested for coating rate, Dv50, specific surface area, and tap density. Each material was used as an active material to prepare the negative electrode of the battery, and assembled into a C2032 coin cell for material discharge capacity testing.

[0141] The modified graphite materials and artificial graphite prepared in the above embodiments and comparative examples were subjected to Raman spectroscopy surface scanning. For the same sample, the I values ​​at 500 different sites were statistically analyzed. D / I G Value, I D / I G A value greater than 0.2 is considered valid; I values ​​from 500 different sites are taken. D / I G The average value indicates the higher the coating rate, meaning a higher degree of coating uniformity.

[0142] The modified graphite materials and artificial graphite prepared in the above embodiments and comparative examples were tested for Dv50 using a Malvern 3000 particle size analyzer. The testing method was in accordance with the national standard method GB / T 24533-2019.

[0143] The modified graphite materials and artificial graphite prepared in the above embodiments and comparative examples were tested for tap density using a BT-313 tap density tester. The testing method was carried out in accordance with the national standard method GB / T 24533-2019.

[0144] The modified graphite materials obtained in each of the above Examples 2 were observed using a transmission electron microscope, and the results were as follows: Figure 2 The TEM image shown shows that the surface of the modified graphite material in Example 2 has a relatively uniform coating layer.

[0145] Using the modified graphite material and artificial graphite provided in the examples and comparative examples of this application as active materials, a C2032 type coin cell was prepared according to the following steps: The graphite negative electrode material, sodium carboxymethyl cellulose, and styrene-butadiene rubber prepared in the examples and comparative examples were mixed evenly at a mass ratio of 95:3:2 to form a slurry, which was then coated onto copper foil. The slurry was dried, rolled, and punched to form the working electrode. The coin cell was assembled in an argon-filled glove box, using lithium metal as the counter electrode, a polyethylene propylene porous membrane as the separator, and a 1M LiPF6 / (EC / EMC = 1:1) electrolyte.

[0146] The button cell battery in this application was tested using the Xinweilan electric tester (model: CT-4008Tn-5V20mA-164). Specifically, this includes:

[0147] 1) First, after each C2032 button cell was placed at room temperature for 10 hours, it was charged and discharged at 1C constant current at 25℃, with the charging and discharging voltage limited to 0.005V to 2V, and its first reversible specific capacity and first coulombic efficiency were tested.

[0148] 2) Subsequently, at 25°C, 3C constant current charge and discharge was performed, with the charge and discharge voltage limited to 0.005V to 2V, to test its reversible specific capacity and 500-cycle performance. The results are shown in Table 1.

[0149] Table 1. Parameters of each embodiment and comparative example

[0150]

[0151] The results above show that, compared to Comparative Example 2 which used phenolic resin as a coating agent, the modified graphite materials in Examples 1-6 achieved a significantly higher coating rate through chemical bonding. Specifically, compared to the uncoated artificial graphite in Comparative Example 1 or the modified graphite material obtained in Comparative Example 2 using phenolic resin as a coating agent, the modified graphite materials in Examples 1-6, which used fluorocarbon resin to coat the artificial graphite, exhibit significantly improved rate performance and cycle performance in secondary batteries.

[0152] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0153] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A method for preparing a modified graphite material, characterized in that, Includes the following steps: Step 1: Oxidize artificial graphite to obtain modified artificial graphite with oxygen-containing functional groups on the surface; Step 2: The modified artificial graphite obtained in Step 1 is chemically bonded to a fluorocarbon resin containing hydroxyl groups, so that the fluorocarbon resin coats the artificial graphite to obtain a coated precursor. Step 3: Carbonize the coating precursor obtained in Step 2 to obtain a hard carbon-coated modified graphite material containing CF bonds.

2. The preparation method according to claim 1, characterized in that, The artificial graphite described in step one has a Dv50 of 8-15 μm and a specific surface area of ​​1.3-1.4 m². 2 / g, tap density is 1.1-1.2g / cm³ 3 The degree of graphitization is 92-94%; And / or, the artificial graphite is oxidized using an oxidizing agent; the oxidizing agent includes at least one of concentrated sulfuric acid, hydrogen peroxide, potassium permanganate solution, or concentrated nitric acid; And / or, a first catalyst is added during the oxidation of the artificial graphite; the first catalyst includes at least one of formic acid, glacial acetic acid, or propionic acid; And / or, the mass ratio of the artificial graphite, the oxidant and the first catalyst is 1:(3-8):(0.5-1); And / or, the temperature of the artificial graphite oxidation reaction is 40-70℃ and the time is 6-10h; after filtering, washing and drying the reaction residue, the modified artificial graphite is obtained.

3. The preparation method according to claim 1, characterized in that, In step two, the fluorocarbon resin has a carbon residue rate of 40-50% and a fluorine content of 15-25%, and based on the fluorocarbon resin, the hydroxyl group content of the fluorocarbon resin is 5-10 wt%. And / or, the fluorocarbon resin has a weight-average molecular weight of 15,000-30,000 g / mol and a molecular weight distribution coefficient of less than 2.

0.

4. The preparation method according to claim 3, characterized in that, The fluorocarbon resin is prepared by dissolving a polymer composition including a variety of polymeric monomers and an initiator in a reaction solvent and reacting at 50-75°C for 5-12 hours. The polymeric monomers include vinyl acetate, hydroxyethyl allyl ether, phenyl acrylate, trifluorochloroethylene, and phenethyl cinnamate, dioctyl phthalate, or diallyl phthalate; wherein, based on the polymeric composition, the hydroxyethyl allyl ether has a mass percentage of 10-15%; the trifluorochloroethylene has a mass percentage of 20-30%; and the total mass percentage of the remaining polymeric monomers is 60-70%. And / or, based on the polymer composition, the initiator is a thermally decomposable initiator with a mass percentage of 1-5%; And / or, the reaction solvent is a benzene-based solvent, and its mass is 1.5-2 times that of the polymer composition.

5. The preparation method according to claim 1, characterized in that, In step two, under a protective atmosphere, the fluorocarbon resin and the modified artificial graphite in a mass ratio of (30-40):(200-300) are dissolved in a solvent and reacted at 80-120℃ for 5-10 hours under the action of a second catalyst. The coated precursor is obtained by vacuum distillation. And / or, the second catalyst is dibutyltin dilaurate, di(dodecylthio)dioctyltin, or stannous isooctanoate; And / or, the mass ratio of the second catalyst to the modified artificial graphite is (0.5-1):(200-300); And / or, the solvent is an organic solvent; the mass ratio of the solvent to the fluorocarbon resin is (150-250):(30-40); And / or, the organic solvent is selected from naphtha, toluene or xylene.

6. The preparation method according to any one of claims 1-5, characterized in that, The coating precursor described in step three is carbonized under a protective atmosphere; And / or, the heating rate during the carbonization process of the coated precursor is 2-5℃ / min, the carbonization temperature is 700-1100℃, and the holding time is 2-5h.

7. The preparation method according to claim 6, characterized in that, The coating precursor is carbonized by staged heating, and the carbonization process includes a first carbonization process and a second carbonization process; in the first carbonization process, the carbonization temperature is 500-700℃ and the holding time is 20-20min; in the second carbonization process, the carbonization temperature is 700-1000℃ and the holding time is 30min-5h.

8. The preparation method according to claim 7, characterized in that, The carbonization process of the coated precursor also includes a third carbonization process; wherein the carbonization temperature is 800-1100℃ and the holding time is 2-5h.

9. The modified graphite material obtained by the preparation method according to any one of claims 1-8.

10. The modified graphite material according to claim 9, characterized in that, The modified graphite material has a core-shell structure; its coating density is >70%, its Dv50 is 10-13 μm, and its specific surface area is 1.4-1.6 m². 2 / g, tap density is 1.2-1.3g / cm³ 3 .

11. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, wherein the negative electrode film layer includes the modified graphite material as described in claim 9 or 10.

12. A secondary battery, characterized in that, The secondary battery includes the negative electrode sheet as described in claim 11.

13. An electrical appliance, characterized in that, The electrical device includes the secondary battery as described in claim 12.